Book Review: Stacey Gutkowski. Secular War: Myths of Religion, Politics and Violence. London and New York: I.B. Tauris, 2014. ISBN: 978-17-80-76535-8. Pp. 320. Hardcover. £68.00. Issue 4 (2014) - Miles, Anne
No abstract available